ISOLATED ENTERIC SPLENIC LESION IN AN IMMUNOCOMPETENT HOST: AN INTERESTING CASE REPORT - A, ANJANA; SINGHAI, PANKAJ; ADHIKARY, RANJEETA; BHAVANA, MALAVALLI V; YADAVALI, REDDI P (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Splenic abscess is often an unrecognized complication of enteric fever. Diagnosis is difficult because of its rarity, insidious onset, and non-specific presentation. We report an interesting case of splenic lesion in an immunocompetent adolescent with no other comorbidities, who presented with history and clinical presentation more suggestive of tubercular etiology. However, culture from the CT-guided fine-needle aspirate grew Gram-negative bacilli, identified as Salmonella Typhi which was sensitive to ampicillin, cotrimoxazole, azithromycin, and ceftriaxone. He responded favorably with oral antibiotics without any further surgical intervention. High degree of clinical awareness with timely and appropriate microbiological evaluation helped into an early definitive diagnosis of enteric splenic abscess. This case highlights that in this era of emerging infections, we should not miss the atypical presentations of the endemic diseases. Safe and minimally invasive radiological intervention with good microbiological correlation is a successful spleen conserving treatment alternative to surgery in suitable patients of splenic abscess.